2010
DOI: 10.1074/jbc.m110.101170
|View full text |Cite
|
Sign up to set email alerts
|

Novel Recombinant Engineered gp41 N-terminal Heptad Repeat Trimers and Their Potential as Anti-HIV-1 Therapeutics or Microbicides

Abstract: Peptides derived from N-terminal heptad repeat (NHR) of the HIV-1 gp41 are generally poor inhibitors of HIV-1 entry, because they tend to aggregate and do not form a trimeric coiled-coil. In this study, we have fused portions of gp41 NHR, e.g. N36 or N28, to the T4 fibritin trimerization domain, Foldon (Fd), thus constructing novel NHR trimers, designated N36Fd or N28Fd, which could be expressed in Escherichia coli cells. The purified N36Fd and N28Fd exhibited SDS-resistant trimeric coiled-coil conformation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 63 publications
2
40
0
Order By: Relevance
“…Potent HIV inhibitors have been designed by sequestering the NHR peptide into a nonaggregating trimeric coiled-coil conformation, which should be able to effectively bind the CHR helix and interfere with six-helix bundle formation. Several design approaches of this type include covalent stabilization of the trimer by disulfide bridges (13)(14)(15) and fusion of NHR segments to trimerization domains (16)(17)(18). Also targeting the CHR region, a protein denoted 5-Helix was engineered by connecting five of six helices that make up the core of the gp41 postfusion structure using short peptide linkers (19).…”
mentioning
confidence: 99%
“…Potent HIV inhibitors have been designed by sequestering the NHR peptide into a nonaggregating trimeric coiled-coil conformation, which should be able to effectively bind the CHR helix and interfere with six-helix bundle formation. Several design approaches of this type include covalent stabilization of the trimer by disulfide bridges (13)(14)(15) and fusion of NHR segments to trimerization domains (16)(17)(18). Also targeting the CHR region, a protein denoted 5-Helix was engineered by connecting five of six helices that make up the core of the gp41 postfusion structure using short peptide linkers (19).…”
mentioning
confidence: 99%
“…We found that these mutants were highly resistant to C34, CP32M, and ADS-J1, but relatively sensitive to T20, suggesting that ADS-J1, C34, CP32M and T2635 share the same target: the pocket region of the HIV-1 gp41 [8890]. Subsequently, we constructed a gp41 NHR-trimer by conjugating the NHR-peptide N36 with a trimerization motif, foldon (Fd), termed N36Fd, as previously described [91], and several N36Fd mutants, including N36(Q64A)Fd, N36(Q64L)Fd, N36(A67G)Fd, N36(A67S)Fd, and N36(Q66R)Fd. We found that the binding affinity of the mutant N36Fd trimers to ADS-J1 was lower than that of the wild-type N36Fd trimer [88], further confirming that the gp41 pocket region is the main target of ADS-J1.…”
Section: Small-molecule Hiv Entry Inhibitors Target Gp41mentioning
confidence: 99%
“…Therefore, establishing an HTS assay using the transiently exposed NHR coiled coil in solution is very challenging. To address this challenge, researchers have employed several strategies, including the design of 5-Helix protein, which contains 5 of the 6 helices that constitute the gp41 trimer-of-hairpins linked into a single polypeptide [100], the addition of a soluble trimeric motif, GCN4 or foldon to a NHR peptide, in order to stabilize the coiled coil [91, 101, 102], and the covalent linking of the peptides in the NHR-trimeric coiled coil [103]. …”
Section: Small-molecule Hiv Entry Inhibitors Target Gp41mentioning
confidence: 99%
“…[98, 99] Another recombinant inhibitor was constructed using peptides derived from the N-terminal heptad repeat. N-terminal peptides are usually not considered to be good candidates because of their propensity for aggregation instead of formation of discrete coiled-coil trimers [100]. The novel protein is made up of N-peptides that have been fused to the T4 fibritin trimerization domain, Foldon.…”
Section: Hiv Gp41 Inhibition: Neutralizing Antibodies Peptides and mentioning
confidence: 99%
“…The novel protein is made up of N-peptides that have been fused to the T4 fibritin trimerization domain, Foldon. This protein was able to form a stable six-helix bundle with the addition of C-peptide and showed potent inhibition against a broad spectrum of HIV strains in vitro [100]. …”
Section: Hiv Gp41 Inhibition: Neutralizing Antibodies Peptides and mentioning
confidence: 99%